The ruined voice in Tom Murphy’s Bailegangaire - Lee, Cheryl Julia (Routledge, 2020)
The dead have a hold on Ireland. Her houses and her pubs, her pages and her stages are full of revenants. These “ghosts in [the] sunlight” 1 are specters conjured by a national imagination, the bronze and marble statues along the street come to life; they are also fathers and mothers, brothers and sisters, the ones with whom we share names and seats at the table, whose eyes tell us how we will grow old, or not. They are reminders of time and time passing, love and the inevitability of love lost. Mostly, they are kept at a distance for fear of the hurting. In Bailegangaire (1985), however, Irish playwright Tom Murphy orchestrates an encounter with the dead, for he suggests that it is in the hurting that a space for meaning to come into being can be located.